Analysis of Viral Hashtag Usage Patterns as a Media for Netizen Character Education (Critical Study of the Global Phenomenon of the Hashtag #dajjal on Twitter) - Purwati; Eldi Mulyana; Nuraly Masum Aprily (Institut Pendidikan Indonesia, 2021)
Hashtags as the key to global social change and education as a tool to optimize it. The research problem in this study is that no research has been found on viral hashtags as a medium for character education for netizens. The formulation of the problem is the pattern of using viral Twitter hashtags and the concept of viral hashtags as a medium for character education for netizens. The aim of this research is to determine the pattern of use of viral hashtags on Twitter social media and also to understand the concept of viral hashtags as a medium for developing netizen character. This research has the benefit of complementing the concept of character education in the technological era and helping people become netizens with character. Research uses: qualitative approach; discourse analysis; research object in the form of viral hashtags; the subject is netizens; sample in the form of the hashtag #dajjal; observation; document records; analysis of character education reviews; and triangulation theory. The results of this research are: 1) viral hashtags are used to share knowledge, prayer, opinions, discussions, social movements, peace mediators, entertainment and personal interests; 2) the concept of character education for netizens, namely viral hashtags as a medium for conveying values ​​knowledge, expressions of value beliefs (values ​​express), value choice declarations (values ​​declare), values ​​clarification, values ​​action, and value control.